Soluble polybenzimidazoles with intrinsic porosity: synthesis, structure, properties and processability - Kumar, Vikas; Chatterjee, Shyambo; Sharma, Pragati; Chakrabarty, Suman; Avadhani, Chilukuri V.; Sivaram, Swaminathan (56Journal of Polymer Science Part A-Polymer Chemistry, 2018)
We have explored two novel comonomers, namely, 4,16-dicarboxyl[2.2]paracyclophane and 5,5,6,6-tetraamino-3,3,3,3-tetramethyl-1,1-spirobi[indane], for the synthesis of co-polybenzimidazoles (co-PBIs) with intrinsic porosity. Both these monomers possess twisted structures that can lead to awkward macromolecular shapes that cannot pack efficiently. The consequences of introducing these two monomers on the structure and properties of PBIs are reported. The random copolymers synthesized are amorphous and possess glass transition temperatures (T(g)s) greater than 400 degrees C. T-g decreases with increasing comonomer content indicating an increase in fractional free volume. The copolymers have low surface area. TEM and BET measurements show evidence of mesopore formation. The copolymers show significant carbon dioxide adsorption. Single chain molecular dynamics simulation of 24-mer repeat units shows intramolecular void spaces arising as a result of distorted polymer chain with reduced conformational mobility. These studies define a new synthetic strategy for bottoms-up synthesis of PBIs with intrinsic porosity. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1046-1057

Stabilization of bis(chlorogermyliumylidene)s within bifunctional PNNP ligand frameworks and their reactivity studies - Sahoo, Padmini; Raut, Ravindra K.; Maurya, Devesh; Kumar, Vikas; Rani, Pooja; Gonnade, Rajesh G.; Majumdar, Moumita (Dalton Transactions, 2019)
The diiminodiphosphine (L-im) and diaminodiphosphines (l-NH and l-NMe) with a bifunctional PNNP ligand framework have been employed to host two [GeCl](+) units leading to the formation of bis(chlorogermyliumylidene) 1-3, respectively. The synthetic route involves a 1:2 stoichiometric reaction between the PNNP ligand and GeCl(2)dioxane and the subsequent addition of two equivalents of chloride abstracting agent. Compound 1 is unstable towards coordinating solvents and Lewis bases, resulting in the displacement of the GeCl unit and the formation of rearranged products 4 and 5. However, the diaminodiphosphine coordinated Ge(ii) bis(monocation)s 2 and 3 proved to be stable and revealed their electrophilic behaviour towards the Lewis bases studied.

Stabilization of the elusive antimony(I) cation and its coordination complexes with transition metals - Kumar, Vikas; Gonnade, Rajesh G.; Yildiz, Cem B.; Majumdar, Moumita (Angewandte Chemie-International Edition, 2021)
Upon stabilization by 5,6-bis(diisopropylphosphino)acenaphthene to form compound 1, the fugitive antimony (I) cation exhibited nucleophilic behavior towards coinage metals. Compound 1 was strategically synthesized at room temperature from SbCl3, the bis(phosphine), and trimethylsilyl trifluoromethanesulfonate taken in a 1:2:3 ratio, whereby the bis(phosphine) plays the dual role of a reductant and a supporting ligand. The generation of 1 involves two-electron oxidation of the ligand to form a P-P bonded diphosphonium dication. Compound 1 was separated from this dication to give both products in pure form in moderate yields. Despite the overall positive charge, the Sb-I site in 1 was found to bind to metal centers, forming complexes with Au-I, Ag-I and Cu-I. Compound 1 reduced Cu-II to Cu-I and formed a coordination complex with the resulting Cu-I species. The effects of the electron-rich bis(phosphine) and the constrained peri geometry in stabilizing and enhancing the nucleophilicity of 1 have been rationalized through computational studies.
Keywords: antimony(I) cation; coordination modes; nucleophilicity; phosphine ligands; reduction